P Pemodelan Matematika dalam Pendidikan - Hardi - Tambunan (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2020)
The ability of students is an important element in the implementation of learning. Knowing students' abilities towards subjects is a must to know the quality of students, teachers and schools, it is also useful for further action for education managers. To find out the overall ability of students to certain subject matter requires an approach that can be used. This study aims to create a mathematical model that can be used to determine students' mathematical abilities after learning at school. Based on the test results, and the completion of the mathematical models created, it can be obtained a description of the cognitive aspects of students' mathematical abilities.